Perancangan Buku Safety Riding dengan Teknik Ilustrasi Karikatur Untuk Menumbuhkan Kesadaran Keselamatan Berkendara Untuk Remaja di Surabaya - Priyogatama, Debby Damar; Bahruddin, Muh; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2016)
Safety riding is a principle or knowledge of riding with safe , where the rider behavior must have adequate levels of security for oneself and others . The rapid growth in the number of vehicles and driver in Indonesia is not balanced with the sufficient increase of enough safety for motorcycle rider, the number of accidents is realy high , especially the case of accidents in adolescents , it is extremely dangerous given the teens are the future generation of a nation . The number of accident rate indicates a lack of awareness of road safety , there are still many who do not consider road safety is something that should be prioritized while ride a motorcycle . Therefore, this study aims to create a book of safety riding with caricature illustration techniques to raise awareness of road safety for young people in Surabaya.Keyword: Safety Riding Book, Awarness, Caricature Illustration, Outstanding